Single-Session Thrombectomy without Thrombolysis for Iliofemoral Deep Vein Thrombosis: A Single-Center Experience of ClotTriever with Evaluation of Predictors for Reocclusion - Qian Yu; Daniel Kwak; Patrick Tran; Ethan Ungchusri; Bowen Wang; Syed Samaduddin Ahmed; Adam Said; Mikin Patel; Jonathan Lorenz; Osman Ahmed (The Arab Journal of Interventional Radiology)
Objective The aim of this study was to determine the effectiveness of a mechanical thrombectomy device in treating iliofemoral deep vein thrombosis (DVT) without thrombolysis and factors associated with post-thrombectomy occlusion.